Exploring the novel sensor system for detecting postural reactions among healthy younger adults: a pilot study - Ooi, Xin Rou (2024)
Background and Objective: Postural control is crucial for stability and fall prevention. However, traditional clinical methods are often subjective, exhibit examiner’s biases and lack sensitivity. Recent sensor-based technologies offer objective measurements but are costly, less portable, and require space and complex setups. This study explores a novel system with six lightweight sensors strategically placed on anatomical landmarks to detect postural changes. The objectives of this study were: (1) analyzing the measurement accuracy of the sensor system in capturing and quantifying real-time postural changes, (2) evaluating the intra-session reliability of the sensors in detecting postural changes over repeated trials, and (3) determining the concurrent validity of the sensor system against the gold standard MDRT.